MORPHOSYNTACTIC ERROR ANALYSIS OF IRAQI MEDICAL STUDENTS’ REPORTS: تحليل أخطاء مورفوسينتيك لتقارير طلاب الطب العراقي (مجلة ديالى للبحوث الانسانية, 2022)
Learners of a foreign or second language are bound to make errors initially. A study, classification and analysis of the errors help to identify the types that are common. Therefore, teachers can focus on dealing with identified errors and ensure that learners avoid committing them. However, when such errors are committed by medical students when writing medical reports, the problem is more aggravated as it concerns the lives of patients. This study deals with the morphosyntactic errors committed by Iraqi students in writing medical reports. It focuses on 30 students pursuing their master degree on a biology course in Medical college of Diyala University, Iraq. The native language of the learners is Arabic. The students have a background of studying English at school and also at college. They are expected to have developed the skills of the English language to a considerable extent. In spite of the previous background, the researcher observed that they commit a number of morphosyntactic errors while writing. Hence, this study of error analysis is attempted to examine the possible cause of each type of error, and whether they are intralingual or interlingual. Further, the researcher has given some suggestions to ESP/EMP teachers who teach English as a foreign language at medical colleges, so that they can make sure that their students avoid committing the detected morphosyntactic errors.